Perceived Impact of Coronavirus Disease 2019 on Surgical Training: A Brazilian Survey - Gerk, Ayla; Naus, Abbie; Carroll, Madeleine; Ponte, Lucas; Salgado, Lucas Sousa; Marrazzo, Enzzo; Secanho, Murilo [UNESP]; Botelho, Fabio; Mooney, David; Ferreira, Roseanne; Ferreira, Júlia Loyola (Elsevier, 2024)
Introduction: Recent studies revealed that coronavirus disease 2019 (COVID-19) negatively impacted residency programs worldwide, particularly procedure-based programs. However, most studies are from high-income countries, with scarce data from low- and middle-income countries. Pandemic effects on surgical training were likely worse in strictly apprenticeship models relying heavily on surgical volume as opposed to competency-based programs. Notably, training programs in Brazil and other low- and middle-income countries follow these strict apprenticeship style frameworks. In this study, we aimed to evaluate the trainees' perceptions of the impact of COVID-19 on their Brazilian surgical programs. Methods: A cross-sectional study was performed using an anonymous survey in Portuguese, distributed via social media platforms to surgical residents enrolled in Brazilian surgery programs. Data collection took place from August 2021 to May 2022. The survey contained 30 questions on the perception of the impact of COVID-19 on surgical training. Results: One-hundred sixty-two residents from 17 different surgical specialties and all five regions of Brazil responded to the survey. Of 162 residents, 145 (89%) believed the pandemic negatively impacted their surgical training. Furthermore, of 162 residents, 153 (94%) reported that elective surgical volume decreased during the pandemic and 91 (56%) were redeployed to assist with COVID-19 management. As a result, 102 of 162 (63%) residents believed their surgical skills were negatively impacted by COVID-19. Yet, 95 of 162 (59%) residents reported their residency programs did not offer resources to mitigate the pandemic's impact on training. Of 162 residents, 57 (35%) reported they did not feel on track for graduation, with no statistical difference between responses by year of residency (P = 0.083). Additionally, 124 of 162 (77%) residents reported that the pandemic negatively affected their mental health, most commonly related to stress at work, stress about transmitting COVID-19, and loss in surgical training. Conclusions: Most of the surveyed Brazilian surgical residents felt the COVID-19 pandemic negatively impacted their training. This leads to believe that the detrimental impacts of the pandemic exposed preexisting weaknesses in the Brazilian surgical training model's dependence on a strict apprenticeship model. Our findings suggest a crucial need to redesign surgical education programs to make residency programs more prepared for changes in surgical volume, evolve the apprenticeship model to competency-based approaches, and unify surgical training standards in low- and middle-income countries.
Keywords: COVID-19; Medical education; Residents; Surgery; Surgical training